Investigation of Thin Film Deposition on Stainless Steel 304 Substrates Under Different Operating Conditions - Nuruzzaman, D. M.; Chowdhury, M. A. (IOP Publishing Ltd., UK, 2016)
In recent times, friction and wear in relation to the deposited carbon films on the steel substrates are important issues for industrial applications. In this research study, solid thin films were deposited on the stainless steel 304 (SS 304) substrates under different operating conditions. In the experiments, natural gas (97.14% methane) was used as a precursor gas in a hot filament thermal chemical vapor deposition (CVD) reactor. Deposition rates on SS 304 substrates were investigated under gas flow rates 0.5 – 3.0 l/min, pressure 20 – 50 torr, gap between activation heater and substrate 3.0 – 6.0 mm and deposition duration 30 – 120 minutes. The obtained results show that there are significant effects of these parameters on the deposition rates on SS 304 within the observed range. Friction coefficient of SS 304 sliding against SS 314 was also investigated under normal loads 5 – 10 N and sliding velocities 0.5 – 1.0 m/s before and after deposition. The experimental results reveal that in general, frictional values are lower after deposition than that of before deposition.